A knowledge transfer model on information technology outsourcing / Rozita Hanapi … [et al.] - Hanapi, Rozita; Abdul Rahim, Emelia; Abu Seman, Sharidatul Akma (2012)
n general terms, outsourcing is a process of contracting out any business processes to outside organization. In Information Technology, outsourcing is contracting out any Information Technology activities or functions such as managing IT infrastructure, software development and software maintenance and support to outside vendors. Nowadays, IT outsourcing could bring many business opportunities to the business company. The main benefits that could be obtained from IT oursourcing are cost reduction and the organization may focus on their core business activities. Knowledge transfer is an important aspect in IT outsourcing. Knowledge transfer in IT outsourcing means the organization could get any new knowledge, for example the technical skills in software development or business skills and strategy from the external vendors during outsourcing activities. As knowledge is very important and crucial for every organization, it is important for the knowledge to be successfully transferred from outsourcing vendor to the outsourcing client. Knowledge sharing within organization can help to increase job performance and productivity. However, it is found that there is no specific knowledge transfer model for IT outsourcing in Malaysia context as this model can give a guideline to the companies in Malaysia, to indicate the most important factors for a successful IT outsourcing knowledge transfer.